2007
DOI: 10.1116/1.2749526
|View full text |Cite
|
Sign up to set email alerts
|

Thermal stability of rare-earth based ultrathin Lu2O3 for high-k dielectrics

Abstract: Articles you may be interested inImpact of ultrathin Al2O3 interlayer on thermal stability and leakage current properties of TiO2/Al2O3 stacking dielectrics J. Vac. Sci.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…Among binary lutetium oxides, only Lu 2 O 3 is the stable solid phase with closed shell trivalent Lu ions, 1 possessing a strong insulating behavior owing to its large band gap (5.8 ± 0.1 eV). 24 On the other hand, lutetium monoxide LuO has existed only as a gaseous phase 5−7 such as various rare earth monoxides with divalent cations (except EuO) because of its largely positive Gibbs formation energy of the solid phase. 1,8 However, various rock-salt type rare earth monoxides were recently synthesized in the form of epitaxial thin films owing to nonequilibrium kinetic growth of the pulsed laser deposition method.…”
Section: Introductionmentioning
confidence: 99%
“…Among binary lutetium oxides, only Lu 2 O 3 is the stable solid phase with closed shell trivalent Lu ions, 1 possessing a strong insulating behavior owing to its large band gap (5.8 ± 0.1 eV). 24 On the other hand, lutetium monoxide LuO has existed only as a gaseous phase 5−7 such as various rare earth monoxides with divalent cations (except EuO) because of its largely positive Gibbs formation energy of the solid phase. 1,8 However, various rock-salt type rare earth monoxides were recently synthesized in the form of epitaxial thin films owing to nonequilibrium kinetic growth of the pulsed laser deposition method.…”
Section: Introductionmentioning
confidence: 99%
“…Rare earth metal oxides as high-κ dielectrics are considered as the replacement of hafnium-based technology [17-19], among which Lu 2 O 3 is the promising one as it shows well-insulating property, large bandgap (5.5 eV), better hygroscopic immunity, good thermal stability, and adequate dielectric constant of approximately 11 [20]. Gao et al reported promising unipolar RS behavior in amorphous Lu 2 O 3 oxide [21].…”
Section: Introductionmentioning
confidence: 99%
“…With well insulating property, large band gap ͑5.5 eV͒, better hygroscopic immunity, good thermal stability, and adequate k value ͑ϳ11͒, Lu 2 O 3 has been studied as high-k candidate to replace silicon oxide as gate dielectrics. 25 However, experimental data related to the resistive switching behavior of lutetium oxide is not clear now. In this paper, we report the unipolar resistive switching properties of the amorphous Lu 2 O 3 films, and a model based on the redistribution of the oxygen vacancy-related defects is suggested to explain its switching behaviors.…”
Section: Introductionmentioning
confidence: 98%